Long-Term Impact of Sustained Knowledge, Confidence, and Clinical Application Following a First-Year Student Pharmacist Diabetes Self-Care Education Program - Candis M. Morello; Eduardo S. Fricovsky (Pharmacy)
With diabetes reaching epidemic proportions globally, it is imperative to increase the number of providers equipped to screen, educate, and help patients achieve glycemic control. This study evaluated the long-term results of student pharmacists attending a first-year Diabetes Self-Care Education Program (DSEP) by measuring knowledge retention, confidence, and clinical applicability of skills learned over time. The DSEP, integrated into the early pharmacy curriculum, is a 9-h training program made up of interactive lectures, glucose monitoring assignments, and active-learning workshops. Following DSEP training, two cohorts of first-year student pharmacists were surveyed annually for 3 and 5 years to assess knowledge retention, confidence, and clinical use of the DSEP content in their practice sites. By the year 1 follow-up survey, the response rate from the pre-survey period for cohort 1 was 88% and 78% for cohort 2; over time, the response rate decreased. For the long-term follow-up surveys, cohort 1 (5 years) and cohort 2 (3 years) demonstrated overall significantly improved sustained knowledge of diabetes (48% higher average test score, p < 0.001), perceived confidence, and clinical ability (over 60% and 76% increases from baseline, p < 0.001). Within 12 months of completing the DSEP, about two-thirds of students applied their training to assist patients with diabetes and their caregivers. Long-term, participants in both cohorts reported educating and screening over 22,000 patients with diabetes and caregivers in multiple clinical settings over 3 years and 5 years, respectively, following DSEP training. The positive impact of improved knowledge, confidence, and clinical applicability of the DSEP training obtained by student pharmacists was sustained for 3 or more years, impacting thousands of patients with diabetes and caregivers. Considering the growing global diabetes epidemic, pharmacy schools around the world should consider implementing an early DSEP program.